Oral Passive Immunization With Plasma-Derived Polyreactive Secretory-Like IgA/M Partially Protects Mice Against Experimental Salmonellosis - Corthésy, Blaise; Monnerat, Justine; Lötscher, Marius; Vonarburg, Cédric; Schaub, Alexander; Bioley, Gilles (Frontiers in Immunology, 2018)
Secretory immunoglobulins have a critical role in defense of the gastrointestinal tract and are known to act by preventing bacterial acquisition. A stringent murine model of bacterial infection with Salmonella enterica Typhimurium was used to examine protection mediated by oral passive immunization with human plasma-derived polyreactive IgA and IgM antibodies (Abs) reconstituted as secretory-like immunoglobulins (SCIgA/M). This reagent has been shown to trigger Salmonella agglutination and to limit the entry of bacterium into intestinal Peyer’s patches via immune exclusion. We now demonstrate that upon administration into ligated intestinal loops, SCIgA/M properly anchors in the mucus and is protected from degradation to a better extent that IgA/M or IgG. Moreover, prophylactic oral administration of SCIgA/M before intragastric infection of mice with a virulent strain of Salmonella enterica Typhimurium allows to protect infected animals, as reflected by reduced colonization of both mucosal and systemic compartments, and conserved integrity of intestinal tissues. In comparison with IgA/M or IgG administration, SCIgA/M provided the highest degree of protection. Moreover, such protective efficacy is also observed after therapeutic oral delivery of SCIgA/M. Either prophylactic or therapeutic treatment with passively delivered SCIgA/M ensured survival of up to 50% of infected mice, while untreated animals all died. Our findings unravel the potential of oral passive immunization with plasma-derived polyreactive SCIgA/M Abs to fight gastrointestinal infections.